Indikasi Wilayah Pengembangan (WP) sebagai Pendekatan Perencanaan dan Pengembangan Wilayah di Kabupaten Kebumen - Iwan Aminto Ardi; Niken Ratna Widiastuti; Hidayati, Solikhah Retno; Mardiana Niken (Institut Teknologi Nasional Yogyakarta, 2024)
The process of regional planning and development requires the right concepts and approaches so that regional planning and development can run effectively and optimally. Kebumen Regency, with its extensive area and diverse regional characteristics, requires an appropriate approach in its regional development planning, so that the implementation of development is targeted and equitable, thereby reducing regional disparities. The study of development area indications aims to determine the grouping of sub-district areas into several clusters of development areas based on similar characteristics. The method used in this study is K-Means Cluster multivariate analysis. The variables used include infrastructure availability, population density, and spatial proximity. Based on cluster analysis, it was found that the Kebumen Regency area can be divided into seven regional clusters, according to the similarity of characteristics. This cluster will later be utilized for the optimization of development according to the characteristics of each regional cluster.